Non-pharmacological interventions for behavioral and psychological symptoms of dementia: A systematic review and network meta-analysis protocol - Li, Ya-Qin; Yin, Zi-Han; Zhang, Xin-Yue; Chen, Zheng-Hong; Xia, Man-Ze; Ji, Lai-Xi; Liang, Fan-Rong (Frontiers in Psychiatry, 2022)
Introduction Dementia patients often experience behavioral and psychological symptoms (BPSD), which severely affect their quality of life and activities of daily living. Non-pharmacological interventions are effective in treating BPSD, according to multiple clinical trials and systematic reviews. However, the optimal non-pharmacological treatment remains controversial. Therefore, the study aims to evaluate and compare multiple non-pharmacological methods for treating BPSD in order to identify the optimal non-pharmacological intervention. Objective This study aims to perform a systematic review and network meta-analysis of evidence on non-pharmacological interventions in the treatment of BPSD, which may potentially guide future research and clinical decisions. Methods In order to select potentially relevant randomized controlled trials (RCTs), 10 academic databases and 3 clinical trial registries will be systematically searched from inception until the 1 October 2022. Two researchers will independently extract information from eligible articles. The primary outcome is the severity of BPSD. Herein, Pairwise and Bayesian network meta-analyses will be conducted utilizing STATA 15.0 and ADDIS 1.16.8. Evidence quality will be assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results Results from this study will be published in peer-reviewed journals or conference reports. Discussion In this study, we aim to comparatively assess the efficacy of various non-pharmacological treatments for BPSD. Findings from this review will help clinicians to make evidence-based treatment decisions. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022352095].